Twenty years of education of pharmacist at the Faculty of Medicine in Niš - Nešić, Ivana (Archives of Pharmacy, 2022)
Considering the lack of a sufficient number of pharmacists, primarily in pharmacies in the Nišava district and Southern Serbia, with the approval of the Ministry of Education, the Department of Pharmacy was formed in 2002 at the Medical Faculty of the University of Niš. Through two accreditation cycles, the curriculum has been updated and harmonized with modern European trends in education of pharmacists. Emphasis is placed on the realization of a larger number of elective courses, increasing the number of hours of professional practice in a real work environment and the development of interprofessional cooperation with future doctors of medicine and dentistry, who are educated at the same faculty. Masters of Pharmacy could from the school year 2008/2009 continue their education in doctoral academic studies, and from 2017 they can professionally improve themselves through health specialization in Pharmacotherapy. The first generation of students of specialist academic studies in Cosmetology will begin their education in the school year 2022/2023. During twenty years of work, cooperation has been established with faculties and institutes in the country and abroad, with which a number of projects financed by national and international institutions have been realized. So far, 867 masters of pharmacy and 14 doctors of medical sciences have been educated. The education of masters of pharmacy continues through the permanent modernization of teaching and educational activities, affirmation of lifelong learning, introduction of new study programs, strengthening cooperation with other educational, scientific and professional institutions as well as economic entities in the country and abroad.